Marko Fernandez Video Approaching COVID-19 Testing Site - Fernandez, Marko::::::::: (2022)
One of two videos taken by Marko Fernandez at a drive through COVID-19 testing facillity. The contributor writes, "The testing site is in parking lot B which is across the street from the Fairgrounds. This is a drive through testing site designed to test people at a high volume while still maintaining social distancing."